Assessment of the natural landscapes and the impact of the waterfalls on the middle basin of the Utcubamba river - Arévalo Gómez, Walter (2008)
This article summarizes the study carried out, the objective of which is to assess the landscape impact of the Utcubamba River Falls, which is part of the research project for the management of natural landscapes for ecotourism purposes in the middle basin of the Utcubamba River. What is remarkable about the study is that it addresses a relatively new aspect; but, very important for the use of natural resources. In the valuation of the landscape there is a clear conflict between different approaches; the method used for the valuation of the landscape units in this work is the one proposed by Ignacio Cañas Guerrero and María A. Ruiz Sánchez. This method is briefly described, and later on, the aim is to combine the different possible approaches in the valuation of the landscape, thus considering physical, artistic and psychological attributes.